Propagation from Geostationary Orbit Satellite to Ground Station Considering Dispersive and Inhomogeneous Atmospheric Environments - Kim, Changseong; Heo, Jun; Jung, Kyung Young; Choo, Hosung; Park, Yong Bae (IEEE Access, 2020)
We propose a novel method to calculate the propagation from a geostationary orbit (GEO) satellite to a ground station considering dispersive and inhomogeneous atmospheric environments with an actual satellite parabolic reflector antenna. The proposed simulation method is based on the hybrid numerical techniques including physical optics (PO), the 3-dimensional (3-D) ray tracing technique, and geometrical optics (GO). The electromagnetic propagation from an actual GEO satellite parabolic reflector antenna to a ground station at Seoul, Korea is calculated using PO. Reflections and refractions at the boundaries of the stratified refractive index model for the atmosphere are then calculated by the ray tracing approach and GO to take into account inhomogeneous atmospheric environments. Our method is verified by comparing with the results with the prediction method of rain attenuation given in ITU-R P.618-13 and the unified model. The comparison generally shows a good agreement. Atmospheric attenuation and boresight errors from a GEO satellite to a ground station are calculated and discussed. As a result of the calculations, when the rainfall rate is 26.19 mm/h, the atmospheric attenuation from a GEO satellite (COMS-1) to a ground station at Seoul, Korea is 12.1621 dB and the boresight error is 0.0336 degrees.
Keywords: Atmospheric attenuation; Atmospheric environment; Electromagnetic propagation; Geostationary orbit satellite; Geostationary orbits; Numerical techniques; Parabolic reflector; Ray-tracing technique; 3-D ray tracing technique; Atmospheric environments; dispersive and inhomogeneous media; geometrical optics; physical optics